A Symposium to Mark the Publication, by New York University Press, of Ian O'Donnell's Prison Life: Pain, Resistance, and Purpose. (March 2023) - Gido, Rosemary; Jeffreys, Derek S.; Behan, Cormac; Edgar, Kimmett; Schmidt, Bethany E.; Mesko, Gorazd; Stohr, Mary K.; Rubin, Ashley T.
Recognizing the major scholarly contributions to criminology by the noted Irish criminologist, Ian O'Donnell, The Prison Journal invited seven contemporary corrections and punishment scholars to offer insights into O'Donnell's new book, Prison Life: Pain, Resistance, and Purpose . Offering contextually rich descriptions of prisoner life, the text features four case study prisons—H Blocks, Northern Ireland; Eastham Unit, Texas; Isir Bet, Ethiopia; and ADX Florence, Colorado, in pivotal time periods and through an individual's custodial career in each institution. The symposium discussants focus on O'Donnell's conceptual framework—the degree of prison integration, system and staff regulation, and legitimacy —and how these reflect the key interactions between punishment and society across time and culture.